Transforming industrial heritage in St. Petersburg Possible futures for the southern industrial belt - Engel, Barbara; Horn, Christian; Sender, Arina; Ziegler, Volker; Rogge, Nikolas (project baikal, 2015)
Together with ITMO University of St. Petersburg, the National Superior School of Architecture of Strasbourg (ENSAS) and the Faculty of Architecture of the Karlsruhe Institute of Technology (KIT) set up a Collaborative Urban Design Studio on the transformation of the southern industrial belt of St. Petersburg. The sustainable redevelopment of postindustrial landscapes into attractive urban districts through new programmatic and spatial possibilities taking into account the sense of place and the unique characteristics of St. Petersburg’s urban geography, the reuse of industrial structures and their adaption to new activities, the designing of spatial structures for lively mixed-use neighbourhoods with housing and work facilities meeting different needs and incomes, are some of the key issues for a common workshop scheduled in November 2015.
Keywords: St. Petersburg; post socialist city; industrial belt; urban transformation; university collaboration; ENSAS; KIT; ITMO